Pedological and isotopic relations of a highland tropical peatland, Mountain Range of the Espinhaço Meridional (Brazil) - Horák,Ingrid (2011)
The evolution of organic matter sources in soil is related to climate and vegetation dynamics in the past recorded in paleoenvironmental Quaternary deposits such as peatlands. For this reason, a Histosol of the mineralotrophic peatland from the Pau-de-Fruta Special Protection Area - SPA, Espinhaço Meridional, State of Minas Gerais, was described and characterized to evidence the soil constituent materials and properties as related to changes in environmental conditions, supported by the isotopic and elementary characterization of soil C and N and 14C ages. Samples were collected in a depression at 1,350 m asl, where Histosols are possibly more developed due to the great thickness (505 cm). Nowadays, the area is colonized by vegetation physiognomies of the Cerrado Biome, mainly rocky and wet fields (Campo Rupestre and Campo Úmido), aside from fragments of Semidecidual Seasonal Forest, called Capões forests. The results this study showed that early the genesis of the analyzed soil profile showed a high initial contribution of mostly herbaceous organic matter before 8,090 ± 30 years BP (14C age). In the lower-mid Holocene, between 8,090 ± 30 years AP (14C age) to ± 4,100 years BP (interpolated age), the vegetation gradually became more woody, with forest expansion, possibly due to increased humidity, suggesting the existence of a more woody Cerrado in the past than at present. Drier climate conditions than the current were concluded ± 2,500 years BP (interpolated age) and that after 430 years BP (14C age) the forest gave way to grassland, predominantly. After the dry season, humidity increased to the current conditions. Due to these climate fluctuations during the Holocene, three decomposition stages of organic matter were observed in the Histosols of this study, with prevalence of the most advanced (sapric), typical of a deposit in a highly advanced stage of pedogenetic evolution.